PENGARUH KEDISIPLINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA CV MUSLIM GALERI DI TANGERANG SELATAN - Setiawan, Agus; Nelsi, Mitri (Journal of Research and Publication Innovation, 2024)
This study aims to measure the effect of discipline and compensation on the performance of CV Muslim Galeri employees in South Tangerang, both partially and simultaneously. The method used is descriptive quantitative with saturated samples, involving the entire population of 70 people. Data collection is done through primary and secondary data. Data analysis uses descriptive techniques, validity, reliability, classical assumptions, quantitative verification, and hypothesis testing. The results showed a strong positive relationship between discipline (X1) and employee performance (Y) with the regression equation Y = 5.067 + 0.843X1, correlation 0.805, and coefficient of determination 64.9%. Hypothesis testing shows a significant effect of discipline on employee performance (t_value11,207 > t_table 1,995), so Ho1 is rejected and Ha1 is accepted. For compensation (X2) and employee performance (Y), a strong relationship was found with a regression equation Y = 12.384 + 0.739X2, a correlation of 0.827, and a coefficient of determination of 50.9%. Hypothesis testing shows a significant effect of compensation on employee performance (t_value8.391 > t_table1.995), so Ho2 is rejected and Ha2 is accepted. Simultaneously, discipline (X1) and compensation (X2) have a significant effect on employee performance (Y) with the regression equation Y = 2.886 + 0.636X1 + 0.283X2, correlation 0.827, and coefficient of determination 67.5%. Hypothesis testing shows the value of f_value 72.576 > f_table 3.134, so Ho3 is rejected and Ha3 is accepted. These results indicate that discipline and compensation have a significant effect on employee performance at CV Muslim Galeri.